Evaluación del etileno y su influencia en el índice de madurez del banano Musa aaa, aguacate Persea americana y papaya Carica papaya. - Moran Gonzales, Josselyn Enelix (2024)
The present research work focuses on the evaluation of ethylene and its influence on the maturity index of banana Musa paradisiacaavocado Persea americanaand papaya Carica papayaat the Technical University of Babahoyo, using ethylene in different dosages. Within the methodology used, a qualitative type was established, with which the qualities of the analyzed fruits, banana, avocado and papaya, were recognized, in order to, through a systematic process, be able to identify the influence of ethylene in the ripening process. of the fruits analyzed. In addition to evaluating its pH, acidity and brix degrees to guarantee the quality of the fruit, a completely randomized block experimental design with an A*B factorial arrangement was used. The factors studied were: Factor A (the values per unit of fruit to be used and factor B (the amount of milliliters of ethylene Etherl in which the fruit will be immersed), corresponding to 9 treatments with 3 replicas, generating 27 experimental units. The study was analyzed through Excel tables, using the SPSS statistical software, this is how it is possible to demonstrate incidence during the maturation process such as the influence of pH range, acidity, brix degrees and maturity index .